Fluidnost eritrocitnih membran pri rakavih bolnikih - študija z elektronsko paramagnetno resonanco - Živec, Katarina (Medicinski razgledi, 2006)
Background: Hypocholesterolemia in cancer patients is a frequent and expected phenomenon. Higher fluidity of plasma membranes (as a result of lower concentration of cholesterol) is a characteristic of most cancer cells. Erythrocytes lack organelles and inner membranes and with that any possibilityof endogenous synthesis of lipids. Changes in serum lipid concentration could be shown in the fluidity of erythrocyte cell membranes. Aim: To compare the fluidity of erythrocyte membranes in cancer patients and in healthy controls in relation to serum lipid concentration, type, stage of cancer and age. Hypothesis: Hypocholesterolemia in cancer patients is the cause, that erythrocyte membranes have higher fluidity. Methods: In prospective study we included 49 cancer patients and 25 healthy controls. We studied the membrane fluidity of isolated erythrocytes by the electronic paramagnetic resonance method. In membranes incorporated spin label gives us information (spectrum) about fluidity in the neighborhood. We also added 0.5 Mcholesterol to erythrocytes samples from healthy individuals and measured thechange in membrane fluidity. Results: Cancer patients in comparison to healthy controls do not have higher erythrocytes membrane fluidity but they dohave significantly lower serum lipid concentrations. Fluidity of erythrocytemembranes is higher in patients with higher total serum cholesterol, HDL and LDL. Addition of cholesterol (in vitro) to erythrocytes of healthy individuals significantly increases the concentration of cholesterol in cell membranes and their 17uidity as well. Conclusions: The surprising result that hypocholesterolemia does not cause higher fluidity of erythrocyte membranes we explained with the existence of membrane domains and changes in metabolism in cancer patients. (Abstract truncated at 2000 characters)
Keywords: Eritrocitna membrana; Neoplasms; Erythrocyte Membrane; Hipolipoproteinemija; Holesterol; Membrane Fluidity; Membranska fluidnost; Hypolipoproteinemia; Cholesterol; Novotvorbe; tumor; Elektronska, spinska resonanca, spektroskopija; Blood; celična membrana; Electron Spin Resonance Spectroscopy; fluidnost; rak (medicina); elektronska paramagnetna resonanca